In vitro antiproliferative effect and induction of apoptosis by Retama monosperma L. extract in human cervical cancer cells - Merghoub, N.; Benbacer, L.; El btaouri, H.; Ait benhassou, H.; Terryn, C.; Attaleb, M.; Madoulet, C.; Benjouad, A.; El mzibri, M.; Morjani, H.; Amzazi, S. (Cellular and Molecular Biology, 2011)
The antiproliferative effect of different extracts obtained from Retama monosperma L. was investigated on human SiHa and HeLa cervical cancer cell lines using a MTT colorimetric assay. The Retama monosperma L. dichloromethane fraction (Rm-DF) was the most active extract, exhibiting a significant cytotoxic activity on both cell lines in a dose-dependent manner, after 72h of treatment. IC50 values obtained were 14.57±4.15µg/ml and 21.33±7.88µg/ml, for SiHa and HeLa cell lines respectively. The morphological features assessment of apoptosis in Rm-DF-treated cells showed a condensation of chromatin and apoptotic bodies, accompanied by a decrease in mitochondrial membrane potential (Î”Î¨m) and an increase in reactive oxygen species in both cell lines. The induction of apoptosis was further confirmed by Western blotting pro-caspase 3, Bcl2 and PARP; caspase 3 activity assay; and Annexin V labelling. Analysis of Rm-DF by CG/MS revealed the presence of five known quinolizidine alkaloids as well as, sparteine (10,97%), L- methyl cytisine (9.11%), 17- oxosparteine (3.49%), lupanine (0.93%) and anagyrine (39.63%). This study shows that Retama monosperma L. extract exhibits a potential anticancer activity against cervical cancer cell lines in vitro through the inhibition of proliferation and induction of apoptosis, which may involve a mitochondria-mediated signaling pathway.